A Literature Review of Factors Contributing to Asthma Relapse - Amalia Septiani; Suyanto Suyanto; Dwi Heppy Rochmawati; Erna Melastuti (GLOBAL HEALTH SCIENCE GROUP, 2025)
Asthma is a chronic respiratory condition characterized by airway narrowing, inflammation, and excessive mucus production. Relapse refers to the recurrence of symptoms, which can be severe and disrupt daily activities, often necessitating additional care, either outpatient or inpatient, sometimes with a longer duration than previous episodes. The objective of this literature review is to examine the factors influencing asthma relapse. This study employed a literature review design. Articles were identified through online databases, specifically Google Scholar and PubMed, using keywords and Boolean operators such as AND, OR, NOT. The search terms included “Factors Associated with Asthma” AND “Relapse Asthma.” The literature search was conducted in November 2024, focusing on articles published between 2020 and November 2024. A total of 683 articles were retrieved from Google Scholar and PubMed. Based on the review of 10 selected studies, it was concluded that asthma triggers may result from biological, environmental, or chemical factors. Factors associated with asthma exacerbations include a history of smoking, gastroesophageal reflux disease (GERD), obesity, nasal polyps, depression, and anxiety. Factors linked to severe asthma exacerbations include atopic conditions and passive smoking as primary indicators.